1983
DOI: 10.1002/app.1983.070280116
|View full text |Cite
|
Sign up to set email alerts
|

Addition polyimides. I

Abstract: SynopsisCrosslinking of 4,4'(bismaleimido)diphenyl ether (BM) was investigated in presence of bis(maminophenyl) methylphosphine oxide (BAP), tris(m-aminopheny1)phosphine oxide (TAP), diaminodiphenyl ether (E) and 3,3-bis(p-aminophenyl)phthalide (AP). These crosslinked resins were examined for thermal stability by thermogravimetric analysis. A slight decrease in initial decomposition temperature, the temperature of maximum rate of weight loss, was observed, though the char yield in nitrogen atmosphere a t 8OOOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 7 publications
0
31
0
3
Order By: Relevance
“…In our earlier articles we have reported the synthesis and characterisation of bismaleimides and chain extentled bismaleimides [1][2][3][4][5][6][7]. Effect of structure on thermal characteristics of bismaleimides was also studied.…”
mentioning
confidence: 99%
“…In our earlier articles we have reported the synthesis and characterisation of bismaleimides and chain extentled bismaleimides [1][2][3][4][5][6][7]. Effect of structure on thermal characteristics of bismaleimides was also studied.…”
mentioning
confidence: 99%
“…The results indicate that this is not influenced by the presence of NH2 groups in the backbone. For maleimide resins, on the other hand, Michael-type addition reactions between the electron-deficient maleimido group and the electron-rich amino group lead to a significant reduction in Texo [8] . If a maleimido group was generated during a retrograde DielsAlder reaction, then a decrease in Texo of nadimides containing -NH2 groups would be expected, but this was not observed in the present work.…”
Section: A Good Correlation Between Observed and Calculated Elementalmentioning
confidence: 99%
“…The maximum and minimum values of tensile stress were 56.6 and 23.6 MPa, with an increase of 3.5% and a decrease of 57%, respectively, respect to the values determined for neat PLA probes. The influence of the considered factors on the mechanical strength is described by the following equation σ t = 40.71 -6.98T* e -7.41T* i + 0.19S* i -2.85T* m + + 5.57P* h -5.1t* c + 0.72S* e (3) which showed that the most influential processing factors were T e , T i and t c (all of them with negative influence), and P h (with positive influence). In order to allow an easier interpretation of results, Fig.…”
Section: Manufacture and Properties Of Compositesmentioning
confidence: 99%